Does Emotional Marketing Play a Crucial Role in the Loyalty of Sharia Bank Customers in Indonesia? - Susminingsih Susminingsih; Ina Mutmainah; Muhammad Nasrullah; Ahmad Hanif Muntahal Fahmi; Nuzulul; Mochamad Yusuf (Shirkah: Journal of Economics and Business, 2026)
Customer loyalty plays a vital role in ensuring the sustainability of Islamic banking institutions; yet, there is no conclusive empirical support concerning whether religiosity or emotional marketing influences customer loyalty more. This study investigates the influences of religiosity, emotional marketing, and customer value on customer loyalty while customer satisfaction acts as the mediator. A survey design was employed involving 258 customers of Sharia banks in Indonesia using purposive and accidental sampling methods. Data were collected via structured questionnaire method while Structural Equation Modeling (SEM) analysis was used in AMOS 23 software for data analysis. The findings demonstrate that religiosity and customer value had a significant positive effect on customer satisfaction, whereas emotional marketing did not. The mediating variable, customer satisfaction, had a significant positive impact on customer loyalty. These results emphasize that customer loyalty was crucial for the sustainability of Sharia banks. The study demonstrates that customer loyalty in Islamic banking is driven more by religiosity than by marketing experiences, leading to greater use of Sharia banking products and services. The findings suggest that Indonesian Sharia banks can enhance loyalty by prioritizing Islamic values through initiatives such as Sharia financial seminars, zakat and waqf consultations, education on Islamic principles, and the development of modern digital services.